The Effect of Auxin Hormone Priming on Seed Germination Indices and Seedling Growth of Triticale (Sanabad Cultivar) under Salt Stress - Amin Haghighi; seyed ata Siadat; Ali Moshatati; Seyed Amir Moosavi (علوم و فناوری بذر ایران, 2023)
In order to study the effect of auxin hormone priming on seed germination indices and seedling growth of triticale under salt stress, an experiment was carried out as a factorial experiment in a completely randomized design with four replications in seed science and technology laboratory of plant production and genetics engineering department of Agriculture Sciences and Natural Resources University of Khuzestan in 2018. Experimental factors were auxin hormone priming (control (no priming), 5 μM auxin in 3 hours, 10 μM auxin in 3 hours, 20 μM auxin in 3 hours, 40 μM auxin in 3 hours, 5 μM auxin in 6 hours, 10 μM auxin in 6 hours, 20 μM auxin in 6 hours and 40 μM auxin in 6 hours) and different salinity levels (include 0, 4, 8, 12, 16 and 20 dS/m). The analysis of variance showed that the effect of priming, salinity stress and the interaction effect of them were significant on all measured traits (except germination percetage) in 1 percent probability level. The comparison of means showed that salinity stress decreased germination traits but hormone priming reduced the negative effect of salinity stress and improved different germination indices. Also, the best concentration of Auxin hormone priming was at 20 μM for 3 hours.